NILAI-NILAI DASAR DALAM MEMBANGUN EKONOMI ISLAM - Latif, Abdul (DIKTUM: Jurnal Syariah dan Hukum, 2014)
The aim of this research is to build a set of objectively verifiable and economic order based on the principle states that noble equality and justice to give birth to the civil society under the protection of Allah. The emergence of Islamic economics is intended to form the framework of the underlying economic growth in order to maintain a harmonious life safety and humane, based on the sources of religious values. Islam emphasizes the principle that every human activity measured by merit and sin, each of which is rewarding necessarily contain the value of worship, while the worship of man in economic activity can be characterized by its ability to do good deeds and fastabiqul khairat, enforce al-adl (justice), which restricts people from do arbitrariness, both for themselves and their environment. Islamic economic characteristics include three basic principles. All three are fundamental and shared set of economic theory in Islam, namely the principle of belief, moral and legal principles (muamalah). Basic economic values of Islam consists of; ownership value, the value of fairness, balance value, the value of freedom, the value of togetherness. Principles and business ethics that is now becoming operational basis of Islamic financial institutions in Indonesia. In practical framework principles and business ethics are implemented in a variety of products and services services Shariah financial institutions that use the mechanism for the results (profit sharing).